Analisis Faktor-Faktor yang Memengaruhi Keputusan Penyedia untuk Memasukkan Penawaran pada Tender Pekerjaan Konstruksi di Kementerian Keuangan - Sancoko, Bambang; Pratama, Bary Rachman (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2020)
The participation level of the construction-work provider tender within the Ministry of Finance did not reach the target. In 2017, the expected participation index was 5, but it was only 4.5 in reality. The purpose of this study was to determine the factors that influence provider’s decision whether to submit tender or not, in the context of construction work within the Ministry of Finance. This study used a survey method with questionnaire, that previously validated using content validity technique, as the data collection instrument. This study found 10 factors that mostly influence providers whether to submit tender or not, in the context of construction work within the Ministry of Finance, i.e.: the labor/equipment availability, documents completeness, tender requirements compliance, accessibility to project site/location, hazard/security level, construction method, project location, tax liability, project site/site condition, and tender duration. It suggested that if the Ministry of Finance wishes to improve its participation index in the construction work auction, it is necessary to pay more attention to these factors when planning, preparing, and implementing procurement process.